Summer Camp Critter Jitters - John, Jory; Climo, Liz (New York : Dial Books for Young Readers, 2021)
A variety of animals with different anxieties about going off to summer camp receive reasurrance, in this story about going to a new place.
Ages 4-8.
Grades 2-3.
Keywords: Camps -- Juvenile fiction; Animals -- Juvenile fiction; Camps -- Fiction; Animals -- Fiction; Picture books